Influence of different processing techniques for prosthetic acrylic resins in the surface roughness parameters: a research article - Margarida Martins Quezada; Carlos Miguel da Costa Gomes Fernandes; Javier Montero Martín; André Ricardo Maia Correia; Patrícia Alexandra Barroso da Fonseca (BMC, 2024)
Abstract Background Different processing techniques are employed to obtain poly (methyl methacrylate) (PMMA) with consistent surface quality in terms of topography and tribological function. The purpose of this research is to evaluate its influence on the surface height distribution. Methods In this research, samples of conventional and CAD/CAM acrylic resins were prepared. The following surface roughness parameters were extracted from the profilometric readings: arithmetic mean roughness (Pa), skewness (Psk) and kurtosis (Pku). Profilometric profiles were additionally obtained. Results The average roughness (Pa) with the conventional technique was significantly higher compared to CAD/CAM (t = 4.595; P < 0.001). Heat-cured resins presented the highest mean Pa (F = 6.975; P = 0.06). Heat-cured and milled resins show lower coefficient variation (CV) values, indicating more consistent surface finishing. The surface profiles revealed distinct characteristics in terms of skewness and kurtosis. Conclusions The surface processing method, chemical composition and resin type significantly influence the surface finishing of the resin. The CAD/CAM resins exhibited superior results in terms of surface arithmetic mean roughness (Pa). However, heat-cured resin revealed to present the better surface consistency.